Campylobacter jejuni isolations from Mexican and Swedish patients, with repeated symptomatic and/or asymptomatic diarrhoea episodes. - Sjögren, E. (Cambridge University Press, 1989)
The presence of different Campylobacter jejuni serotypes in Swedish patients with diarrhoea and in Mexican patients with or without diarrhoea was investigated with special reference to repeated isolations during the course of infection and to symptomatic and asymptomatic episodes. The study included 136 C. jejuni isolates from 62 Mexican children and 173 isolates from 68 Swedish patients. The bacteria were serotyped for heat-stable (HS) and heat-labile (HL) antigen. Swedish patients, all with symptoms, were in general only infected with one serotype and were rarely reinfected. Mexican patients on the other hand were in general infected with mixed serotypes and frequently reinfected without symptoms with new, different serotypes, a finding which is in concordance with a theory of an induced immunity to surface antigens.